Do Radical-Right Parties Use Descriptive Representation Strategically? A Replication of Weeks et al. (2023) - Benjamin Guinaudeau; Michael Jankowski (Institute for Replication (I4R), 2024)
When do populist radical-right parties (PRRP) foster the (descriptive) representation of women? In a recently published paper, Weeks et al. (2023) coin the concept of 'strategic descriptive representation'. When facing electoral struggles, PRRP would exploit the existing gender gap and strategically increase the descriptive representation of women to attract female votes and fare better in the election. Using data on 58 elections across 19 countries, the authors test their argument and find conclusive evidence supporting it. In this paper, we offer a replication of the study. First, we assess the numerical reproducibility of the published findings ('verification'). Second, we investigate the 'robustness' of the findings and evaluate the results under alternative model specifications. While our replication study identifies minor issues with the verification and some of themodel specifications, itmost importantly shows that the main results of the paper are driven by a single outlier. The paper's key finding is hence contingent on the inclusion of a single observation (French Front National in 2012), which is a questionable observation as it only elected two MPs, one of whom was a woman. Additionally, this woman's election was seemingly caused by a combination of idiosyncratic factors discussed in the study. Once the case is excluded from the analysis the key model parameter shrinks close to zero and loses its statistical significance. Accordingly, in light of our findings, there is no clear evidence supporting strategic descriptive representation and electoral pressures do not seem sufficient to encourage PRRP to increase their share of female representatives. Correcting this empirical finding has important implications for both understanding PRRP's electoral strategies and women's representation.
Keywords: 330; descriptive representation; women; populist radical-right; replication; robustness; small-N studies